PENINGKATAN KINERJA UMKM DITINJAU DARI MODEL PENGELOLAAN KEUANGAN, SUMBER DAYA MANUSIA, STRATEGI PEMASARAN, DUKUNGAN PEMERINTAH DAN UMUR USAHA - Komala Ardiyani; Syafnita Syafnita (Fakultas Ekonomi Universitas Pekalongan, 2021)
This study aimed to examining the influence of financial management model, human resources competencies, marketing strategies, government support and business age influence the improvement of MSME performance. The study sample of 64 MSMEs in Pekalongan. Data analysis techniques used was multiple linear regression. The results of study prove that the financial management model, human resources competencies, marketing strategies do not have a positive effect on improving the performance of MSMEs. However, government support and business age have a significant effect on improvement of MSME performance